“Once upon a time [...]”: Stimulating management research through vignettes - Bezerra, Joacil Carlos Viana; Coelho, Ana Lúcia de Araújo Lima (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
This methodological essay aims to present and reflect on some aspects to be considered when constructing and using vignettes as a data collection instrument. Characteristics, advantages and possible limitations of vignettes, practical circumstances of use, and frequently used formats are presented. These jointly-addressed aspects contribute to using vignettes in research in Administration, regardless of the perspective of the studies. As the vignette is a data collection instrument fairly used in Administration, this article can guide future researchers serving as a source for those more interested in understanding the characteristics of carrying out a study using vignettes.